Meracik Kesuksesan: Aspek Kelayakan Usaha di Era Milenial Pada Bedhag Kopi Kabupaten Jember - Fitri Ayuandika; Dewi Musliha; Shonya Putri Asalisa; Tabina Shelawangsa Putri Rifa’i; Silvia Agustin; Ahmad Hisyam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Bedhag Kopi is an MSME that enables local products to compete at the global level. Bedhag Kopi is a coffee shop and roaster owned by Mr. Donny Agustinus Waluyo, SE. Bedhag Kopi not only focuses on coffee production, but also builds an integrated system from upstream to downstream, starting from opening a small shop with a local Jember coffee menu, a coffee production house, to becoming a Course and Training Institute (LKP) in the coffee sector. The aim of this research is to analyze aspects of business feasibility in Bedhag Kopi, Jember Regency. The research method in solving this research problem uses descriptive qualitative. This research was written using library research and field research designs. This research uses primary data sources, namely data obtained directly by researchers as research objects. Based on the results of the discussions explained, this business has met the requirements needed to operate, the location and production process have met strategic standards, but there is a need to ensure consistent availability of raw materials. The strategies implemented are quite diverse and focus on local markets, so as to improve product and service quality.